Nilai dan Makna Tarian Tebe di Desa Babotin Maemina Kecamatan Botin Leobele Kabupaten Malaka - Intan Mutiara Iriani Romiro; Yohanis K. Tampani; Antonius Bere; Yuditha Sofiana Kofi; Augusta De Jesus Magalhaes (Politeknik Kampar, 2024)
This research was conducted by Intan Mutiara Iriani Romiro with the title